Peran Guru dalam Menciptakan Lingkungan Pembelajaran yang Efektif dengan Cara Pengelolaan Kelas yang Menarik - Habsy, Bakhrudin All; Azizah, Najwa Hikmahtul; Viola, Nadin Putri; Mahendra, Wiratama (Lembaga Yasin AlSys, 2024)
Classroom management is a key element in achieving a successful learning process. Its significance lies in the substantial impact it has on students' learning achievements. This article aims to provide insights and practical guidance for creating a conducive, safe, and organized classroom environment. Key focuses include classroom management strategies such as implementing clear rules, providing positive feedback, and understanding individual student needs. Teachers are expected to motivate students, minimize disruptions, and enhance their academic achievements, leading to an overall optimal learning experience. The success of effective classroom management is considered a fundamental foundation for achieving successful educational outcomes.